Competitive antagonistic action of laccase between Trichoderma species and the newly identified wood pathogenic Ganoderma camelum - Umar, Aisha; Elshikh, Mohamed S.; Aljowaie, Reem M.; Hussein, Juma Mahmud; Dufossé, Laurent; Wu, Chenghong; Lu, Junxing (Frontiers in Microbiology, 2024)
Ganoderma, a well-known genus of Ganodermataceae, has led to the extinction of several tree species due to its pathogenicity. This study focused on exploring the pathogenic effect of newly identified Ganoderma species in trees and their competitive efficiency against Trichoderma species. Ganoderma camelum sp. nov. is characterized by small sessile basidiomata and a velvety, soft, camel-brown pileus. Phylogenetic analysis and ITS rDNA sequences indicated that the species were Trichoderma and Ganoderma camelum. Both fungal species antagonistically competed by secreting laccase. The laccase of G. camelum, with a value of 8.3 4.0 (U/mL), demonstrated the maximum competitive activity against the Trichoderma species. The laccase of T. atroviride (2.62 U/mL) was most effective against the pathogenic action of the novel G. camelum. The molecular weights of laccase were determined by SDS-PAGE (62.0 kDa for G. camelum and 57.0 kDa for T. atroviride). Due to the white rot induced by this Ganoderma species in the host tree, G. camelum showed the highest percentage inhibition of radial growth (76.3%) compared to T. atroviride (28.7%). This study aimed to evaluate the competitive antagonistic activity of Ganoderma and Trichoderma on Malt extract agar media during the white rot disease of the host tree. This study concluded that the laccase of G. camelum caused weight loss in rubber wood blocks through laccase action, indicating tissue injury in the host species. Therefore, it was also concluded that G. camelum was more effective in the pathogenic action of the host and resisted the biological action of T. atroviride. In principal components analysis (PCA), all the species used with laccase have a very strong influence on the variability of the system. The PIRG rate (percentage inhibition of radial growth) and laccase activity were strongly and positively correlated.